"تقييم واقع توافر مبادئ إدارة الجودة الشاملة في المنظمات" دراسة حالة الشركة العامة لمرفأ طرطوس (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدفت هذه الدراسة إلى التعرف على واقع تطبيق إدارة الجودة الشاملة في الشركة العامة لمرفأ طرطوس, تم الاعتماد على المنهج الوصفي التحليلي لدراسة الظاهرة كما هي على أرض الواقع, وتم توزيع(150) استبانة تضمنت مبادئ إدارة الجودة الشاملة ( المفهوم المدرك لإدارة الجودة الشاملة, دعم الإدارة العليا, نمط القيادة, نظم التعليم والتدريب, التوجه بالعميل, التحسين المستمر, أسلوب حل المشكلات واتخاذ القرارات, نمط الاتصالات, تقييم الأداء, التعاون والعمل الجماعي, الحوافز والأجور, الإبداع والابتكار), تم استخراج المتوسطات الحسابية والانحرافات المعيارية ومعامل الاختلاف للتأكد من وجود هذه المبادئ على أرض الواقع, وتم الاعتماد على اختبار(T-TEST ONE SIMPLE) للتأكد من وجود فروق إحصائية أم لا وذلك بالاعتماد على البرنامج الإحصائي (SPSS 21). وتم التوصل إلى مجموعة من النتائج أهمها عدم تطبيق إدارة الجودة الشاملة في الشركة العامة لمرفأ طرطوس, على الرغم من وجود بعض الإيجابيات التي تساعد في عملية التطبيق, وأوصى الباحث بضرورة اهتمام وتبني الإدارة العليا لمفهوم إدارة الجودة الشاملة, وإيمانها به ووضع الآليات اللازمة لعملية تطبيقه, ووضع خطة طويلة الأجل لعملية التنفيذ, وضرورة عقد دورات تدريبية وتثقيفية لتعريف العاملين في الشركة العامة لمرفأ طرطوس بمفهوم إدارة الجودة الشاملة, وماهي الفوائد التي سوف تجنيها الشركة من خلال عملية التطبيق. This study aimed to identify the fact implement total quality management in General company for Tartous, rely on descriptive analytical study of phenomena as they are on the ground, were distributed (150) identification included principles of TQM (total quality management conscious concept. Senior management support, leadership style, education and training systems, customer orientation, continuous improvement, problem solving and decision making style, communication style, performance evaluation, collaboration and teamwork, incentives and remuneration, creativity and innovation), extracted arithmetic and distractions Standard deviation to ensure these principles on the ground, and was relying on test (T-TEST ONE SIMPLE) To ascertain whether or not statistical differences based on statistical software (SPSS 21). The most important results of the group not to apply total quality management in General company for Tartous, although there are some pros that assist in the application process, the researcher recommended that need attention and build upper management the concept of total quality management, and her faith and develop mechanisms For its application, and a long-term plan to the implementation process, and the need for training and educational sessions to define public company workers Tartous concept of total quality management, and what benefits that will accrue to the company through the application process.